2002
DOI: 10.1002/lsm.10129
|View full text |Cite
|
Sign up to set email alerts
|

In situ light dosimetry during photodynamic therapy of Barrett's esophagus with 5‐aminolevulinic acid

Abstract: Background and Objectives: Previous studies with PhotoDynamic Therapy (PDT) in bladder and bronchi have shown that due to scattering and reflection, the actually delivered fluence rate on the surface in a hollow organ can be significantly higher than expected. In this pilot study, we investigated the differences between the primary calculated and the actual measured fluence rate during PDT of Barrett's Esophagus (BE) using 23 independent clinical measurements in 15 patients. Study Design/Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…PDT light delivery for the esophagus is unique because the esophagus is a hollow organ in which reflected light enhances the light fluence that is delivered directly from the fiber optic light source. Panjehpour et al (10) and van Veen et al (11) measured the actual light fluence at the mucosal surface and found that it was 1.5 to 3.9 times higher than expected. Mackenzie et al (12) reported that esophageal 5-aminolaevulinic acid-PDT treatment success was correlated to the administered PDT light dose.…”
Section: Discussionmentioning
confidence: 89%
“…PDT light delivery for the esophagus is unique because the esophagus is a hollow organ in which reflected light enhances the light fluence that is delivered directly from the fiber optic light source. Panjehpour et al (10) and van Veen et al (11) measured the actual light fluence at the mucosal surface and found that it was 1.5 to 3.9 times higher than expected. Mackenzie et al (12) reported that esophageal 5-aminolaevulinic acid-PDT treatment success was correlated to the administered PDT light dose.…”
Section: Discussionmentioning
confidence: 89%
“…There was no statistically significant difference between APC and MPEC in terms of the efficacy to achieve endoscopic and histological reversal of BE. Although the number of available randomized controlled therapeutic trials is limited, these conclusions are supported by a large amount of experimental and clinical data and with the underlying pathophysiology of BE [6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 92%
“…Several new techniques have been reported to produce successful ablation of BE, including multipolar electrocoagulation (MPEC) [6,7], argon plasma coagulation (APC) [8,9], photodynamic therapy (PDT) [10][11][12], and endoscopic mucosal resection [11,12]. The results of a number of studies suggest that these techniques are of a similar efficacy and that major side-effects are unlikely [13][14][15].…”
Section: Introductionmentioning
confidence: 97%
“…This fluence rate build-up varies with the geometrical shape and tissue optical properties (scattering and absorption), and has been reported to be as high as a factor of 7.5 in the bladder [8]. In another study, we have measured fluence rate variations during PDT of Barrett's oesophagus [9]. The results showed a dramatic variation between patients, with fluence rate build-up factors ranging from 1.5 up to 4.…”
Section: Introductionmentioning
confidence: 92%